Unemployment Prevention System Formation - Ginevičius, Romualdas; Stankevičienė, Asta (Ekonomika, 1999)
Unemployment prevention is analysed in the article as barring the way by which unemployment appears and develops. Measures that would allow to decrease unemployment to its natural level or might slow down increase of unemployment are discussed in the article.Prevention of unemployment as independent problem is not explored yet and exists in decomposed form of separate surveys and programs now.Structure of unemployment prevention system on the macro level consists of: population quality improvement, bringing up of person in a family and at school, training, long-life-learning, economy regulation measures, employment policy. Unemployment prevention measures on the micro level are being realized at the enterprises.In order to guaranty unemployment all-round prevention measures it is purposeful to format unemployment prevention program on the national level. Labour market monitoring needs to become an important element of such program.